RETRACTED: Rethinking sustainable energy development for green energy recovery: Empirical dynamism of oil prices shock - Leng, Feng (Frontiers in Energy Research, 2022)
The purpose of the study is to test the role of market timing between oil price shock and energy efficiency mitigation in ASEAN countries. To achieve the study objective, a persistence econometric modeling technique is applied. The results revealed that oil prices are now the other main source of energy efficiency mitigation in ASEAN economies. Market timing-based factors are replaced with for oil price shock to increase, warranting a collaborative environment. Moreover, green financing loan schemes invest both public and private funds in energy efficiency mitigation to capitalize on a cleaner environment by controlling the oil price shock. The consideration and application of financial consideration for sustainable innovation-financing projects or companies is limitless. Providing for screening CO2 emission reduction and cooperation proposals with speedy greenhouse gas reduction rates might have large opportunity costs. There may be a case for governments to increase industrial growth, improve resource efficiency, and increase factor productivity while tackling energy efficiency. Economic growth in ASEAN may have an even greater influence on greenhouse gas reduction than in other countries. On such points, there is a need to pay attention. If the suggested policy suggestions are implemented successfully, they would help enhance the scope of financing considerations for sustainable innovation to uplift energy efficiency mitigation through market timing-based mechanisms.